The impact of high-altitude migration on cardiac structure and function: a 1-year prospective study - Deng, Ming-Dan; Zhang, Xin-Jie; Feng, Qin; Wang, Rui; He, Fen; Yang, Feng-Wu; Liu, Xian-Mei; Sun, Fei-Fei; Tao, Jie; Li, Shuang; Chen, Zhong (Frontiers in Physiology, 2024)
The trend of human migration to terrestrial high altitudes (HA) has been increasing over the years. However, no published prospective studies exist with follow-up periods exceeding 1 month to investigate the cardiac change. This study aimed to investigate the cardiac changes in 122 Chinese healthy young male lowlanders following long-term migration to HA. The participants were divided into 2 groups: those migrating to altitudes between 3600 meters and 4000 meters (low HA group, n=65) and those migrating to altitudes between 4000 meters and 4700 meters (high HA group, n=57).Traditional echocardiographic parameters were measured at sea level, 1 month and 1 year after migration to HA. All 4 cardiac chamber dimensions, areas, and volumes decreased after both 1 month and 1 year of HA exposure. This reduction was more pronounced in the high HA group than in the low HA group. Bi-ventricular diastolic function decreased after 1 month of HA exposure, while systolic function decreased after 1 year. Notably, these functional changes were not significantly influenced by altitude differences. Dilation of the pulmonary artery and a progressive increase in pulmonary artery systolic pressure were observed with both increasing exposure time and altitude. Additionally, a decreased diameter of the inferior vena cava and reduced bicuspid and tricuspid blood flow velocity indicated reduced blood flow following migration to the HA.Consequently, 1 year of migration to HA is associated with decreased blood volume and enhanced hypoxic pulmonary vasoconstriction. These factors contribute to reduced cardiac chamber size and slight declines in bi-ventricular function.